Regeneration of industrial heritage: a study on the feasibility of expanding into campus space - Xu, Jingjing; Puntien, Pisit; Inkuer, Akapong; Mayusoh, Chanoknart (Edelweiss Applied Science and Technology, 2024)
With the rapid pace of urbanization, campuses are confronted with the challenge of increasingly limited land resources. Traditional campus planning has proven inadequate in meeting the growing educational demands. In this context, exploring the feasibility of repurposing industrial heritage sites for campus space has emerged as a crucial research topic, offering valuable opportunities to expand campus facilities. This paper takes the regeneration design of industrial heritage along the Jiangsu Canal as an illustrative example and analyzes its potential value, modes of reuse, and design strategies. It further investigates how these sites can be transformed into educational spaces within a campus setting. Through practical applications in industrial heritage regeneration design, this paper explores three dimensions: adaptive integration with external spatial environments, functional replacement within internal structures, adaptive reconstruction of space layouts, and renewal of architectural forms. Ultimately, feasible strategies for regenerating and expanding industrial heritage into campus spaces are summarized herein, providing novel ideas and methodologies for future campus expansion endeavors. Concurrently, we hope to raise awareness among all sectors of society regarding the protection and reuse of industrial heritage while collectively promoting sustainable development in this field.